2012
DOI: 10.1097/prs.0b013e31823ae90c
|View full text |Cite
|
Sign up to set email alerts
|

The Three Dermoglandular Flap Support in Reduction Mammaplasty

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite some data suggesting that BMI does not significantly affect complication rates after reduction mammaplasty, 3,25,34 our findings support previously published studies identifying BMI as a predictor of postoperative complications in breast reduction. [8][9][10][11][12][13][14][15][16][17][18][19][20][21]29,30 Interestingly, obesity did not appear to be an independent risk factor for major surgical complications (deep infection and/or unplanned return to the operating room). The increased rate of overall complications in obese patients in this study may be due to a higher incidence of wound dehiscence and other nonoperative healing problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some data suggesting that BMI does not significantly affect complication rates after reduction mammaplasty, 3,25,34 our findings support previously published studies identifying BMI as a predictor of postoperative complications in breast reduction. [8][9][10][11][12][13][14][15][16][17][18][19][20][21]29,30 Interestingly, obesity did not appear to be an independent risk factor for major surgical complications (deep infection and/or unplanned return to the operating room). The increased rate of overall complications in obese patients in this study may be due to a higher incidence of wound dehiscence and other nonoperative healing problems.…”
Section: Discussionmentioning
confidence: 99%
“…These commonly include the inferior pedicle 13 and vertical mammaplasty, 14 as well as other modifications. 15,16 Nevertheless, the benefits of reduction mammaplasty must be weighed against the potential costs of complications. Recent studies have shown that patient age, 17 weight, [18][19][20][21] and smoking status [22][23][24][25] may have an adverse impact on their overall outcomes.…”
mentioning
confidence: 99%